IL-38 Gene Deletion Worsens Murine Colitis - de Graaf, Dennis M.; Wang, Ruth X.; Amo-Aparicio, Jesús; Lee, J. Scott; Dowdell, Alexander S.; Tengesdal, Isak W.; Marchetti, Carlo; Colgan, Sean P.; Joosten, Leo A. B.; Dinarello, Charles A. (Frontiers in Immunology, 2022)
IL-38 is a recently discovered cytokine and member of the IL-1 Family. In the IL-1 Family, IL-38 is unique because the cytokine is primarily a B lymphocyte product and functions to suppress inflammation. Studies in humans with inflammatory bowel disease (IBD) suggest that IL-38 may be protective for ulcerative colitis or Crohn’s disease, and that IL-38 acts to maintain homeostasis in the intestinal tract. Here we investigated the role of endogenous IL-38 in experimental colitis in mice deficient in IL-38 by deletion of exons 1-4 in C57 BL/6 mice. Compared to WT mice, IL-38 deficient mice subjected to dextran sulfate sodium (DSS) showed greater severity of disease, more weight loss, increased intestinal permeability, and a worse histological phenotype including increased neutrophil influx in the colon. Mice lacking IL-38 exhibited elevated Nlrp3 mRNA and protein levels, increased caspase-1 activation, and the concomitant increased processing of IL-1β precursor into active IL-1β. Colonic expression of IL-1α, an exacerbator of IBD, was also upregulated. Myeloperoxidase protein and Il17a, and Il17f mRNA levels were higher in the IL-38 deficient mice. Daily treatment of IL-38 deficient mice with an NLRP3 inhibitor attenuated diarrhea and weight loss during the recovery phase. These data implicate endogenous IL-38 as an anti-inflammatory cytokine that reduces DSS colitis severity. We propose that a relative deficiency of IL-38 contributes to IBD by disinhibition of the NLRP3 inflammasome.